2005
DOI: 10.1098/rspb.2005.3304
|View full text |Cite
|
Sign up to set email alerts
|

Mitosis, stature and evolution of plant mating systems: low-Φ and high-Φ plants

Abstract: There is a long-recognized association in plants between small stature and selfing, and large stature and outcrossing. Inbreeding depression is central to several hypotheses for this association, but differences in the evolutionary dynamics of inbreeding depression associated with differences in stature are rarely considered. Here, we propose and test the F model of plant mating system evolution, which assumes that the per-generation mutation rate of a plant is a function of the number of mitoses (F) that occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
130
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(132 citation statements)
references
References 57 publications
2
130
0
Order By: Relevance
“…Thus, selective interference becomes (proportionally) more important as s declines. Scofield and Schultz (2006) hypothesize that selective interference is responsible for the rarity of highly selfing, long-lived plants. It is thus important to determine the region of parameter space over which this process has substantial effects.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, selective interference becomes (proportionally) more important as s declines. Scofield and Schultz (2006) hypothesize that selective interference is responsible for the rarity of highly selfing, long-lived plants. It is thus important to determine the region of parameter space over which this process has substantial effects.…”
Section: Discussionmentioning
confidence: 99%
“…For both B. tarairi and C. laevigatus, movement of seeds between forest patches may prevent local extinction of small, isolated populations and contribute to gene flow among populations. Inbreeding appears to be particularly detrimental in large-statured plants (trees and shrubs), with inbred offspring almost never surviving to maturity [54], including in two New Zealand trees [55]. Consequently, fragmented tree populations may be particularly vulnerable to extinction [54], and even more dependent on their dispersers.…”
Section: Discussionmentioning
confidence: 99%
“…In C. atlantica, sex allocation to male and female functions is highly variable and Krouchi et al (2004) have found that this variation is stable at least across several years. From an evolutionary perspective, such a tendency to dioecy in trees can be interpreted in the light of ID avoidance (Scofield and Schultz, 2006). Our selfing rate estimates might be down biased because they were computed from the number of mature seeds and not directly from the number of fertilized ovules.…”
Section: Selfing Rate and Inbreeding Depression In Cedrusmentioning
confidence: 99%
“…ID that is caused by a small number of recessive genes that have major deleterious effects on fitness is expected to vary among individuals depending on their genotype at these few major genes and, therefore, to respond rapidly to selection. Purging is less efficient when selfed offspring do not contribute to the next generation (Scofield and Schultz, 2006), or when dominance and epistatic interactions among major genes occur (Williams et al, 2003). By contrast, ID because of many genes with small individual effects is not expected to vary drastically among individuals and is less easily purged in the population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation